Influence of static electric field on cognition in mice. Issue 4 (3rd July 2016) - Xu, Yaqian; Wu, Sixia; Di, Guoqing; Ling, Ping; Jiang, Jianhua; Bao, Hailong
ABSTRACT: With the rapid development of high voltage direct current transmission, the possibility of health effects associated with static electric field (SEF) has caused wide public concern. To examine the effects of long-lasting, full-body exposure to SEF on cognition, Institute of Cancer Research mice were exposed to SEF for 35 d. The intensities of SEF in experimental group I (EG-I), experimental group II (EG-II) and control group (CG) were 2.30∼15.40 kV/m, 9.20∼21.85 kV/m and 0 kV/m, respectively. The performance in learning and memory of mice were tested by Morris water maze (MWM) on days 2∼6, 16∼20 and 30∼34 during the exposure period. The concentrations of hippocampal amino acid neurotransmitters were evaluated on days 7, 21 and 35. Results showed that the latency in the MWM test had no significant difference among the EG-I, EG-II and CG ( P > 0.05) during the exposure period. The percentage of time spent in the target quadrant was significantly decreased in the EG-II on day 34 during the exposure period ( P < 0.05), whereas the percentage of time spent in the opposite quadrant increased markedly ( P < 0.01). The glutamate and gamma-aminobutyric acid concentrations showed no significant differences among the EG-I, EG-II and CG ( P > 0.05) during the exposure period. These results indicated that long-lasting, full-body exposure to SEF with certain intensity would not cause significant influence on learning ability, but it might associate with memory impairment of receptors. Meanwhile, this effect of memory impairment was dose-dependent and not causally linked to the glutamate and gamma-aminobutyric acid levels in the hippocampus.